Gastric adenocarcinoma in Situs inversus totalis: a case study and literature review - Sun, Bo; Xu, Ping; Kong, Pengfei; Fang, Yantian; Fu, Hong (Frontiers in Oncology, 2023)
Background: Situs inversus totalis (SIT) is an uncommon disorder characterized by mirror-image anatomy, which can present unique challenges and potential vascular anomalies in surgical interventions, particularly in gastric cancer patients.We aim to delineate a rare case of gastric adenocarcinoma in a SIT patient and conduct a thorough review of the existing literature concerning surgical strategies, vascular anomalies, and outcomes observed across varied geographic locales and technological approaches.Methods: A thorough examination of a case involving a 39-year-old male SIT patient who underwent a successful distal gastrectomy with D2 lymph node dissection is presented alongside an expansive literature review. The review encompasses 47 articles, collating data on surgical approaches and vascular anomalies across 49 patients diagnosed with SIT and gastric cancer.The patient underwent curative distal gastrectomy and Billroth II with Braun anastomosis within 95 minutes, incurring minimal intraoperative blood loss (100ml).Postoperative pathology confirmed moderately to poorly differentiated gastric adenocarcinoma (pT3N0M0), with no signs of recurrence or metastasis after 6 months of S-1 adjuvant chemotherapy. The literature review revealed vascular anomalies in approximately 20% of reported cases, accentuating its surgical significance.Noteworthy variations in surgical strategies, operative times, blood loss, and complications across different surgical modalities were observed, providing a comprehensive view into the practical management of such cases.Despite the inherent challenges associated with SIT, various surgical techniques can be successfully applied with meticulous preoperative planning and understanding vascular anomalies. This compilation of diverse surgical experiences across numerous documented cases seeks to provide a consolidated resource for refining surgical strategies and enhancing postoperative outcomes for gastric cancer patients with SIT, underscoring the imperativeness of further research in this niche domain.